Studies on Interfaith Relations: Latest Input for Authority Management Review (AMR) in Malaysia - Syed Ismail al-Qudsy, Sharifah Hayaati; Abdul Majid, Mahmood Zuhdi; Yousif, Ahmad F.; Abdullah, Osman Chuah; Marina Munira Abdul Mutalib (Routledge, 2024)
Indexed by SCOPUS